A simple resolver-to-DC converter - Kaewpoonsuk, Anucha; Petchmaneelumka, Wandee; Kamsri, Thawatchai; Riewruja, Vanchai (My University, 2006)
In this paper, a simple resolver-to-dc converter is presented. The realization method is based on the proposed OTA-based sin-1 function circuit. The proposed converter provides a simple configuration and produces an output signal, which is linearity proportional to the shaft angle. Performances of the proposed circuit are discussed in detail and confirmed by the experimental results. © 2006 ICASE.
Keywords: Resolver converter; Resolver-to-dc; Sin-1 function